Pengaruh Keahlian Profesional, Independensi, Tingkat Pendidikan dan Pengalaman Kerja terhadap Kinerja Pengawas Kas BPR - Cahyadi, Hanafi; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 30 No 11 (2020), 2020)
The purpose of this study was to determine the effect of professional expertise, independence, level of education and work experience on the performance of BPR Lestari Bali's cash supervisors. The sample collection technique used is the purposive sampling method. The determined number of samples was 31 Cash Supervisors at PT BPR Lestari Bali. The data analysis technique used is multiple linear regression analysis. The analysis showed that professional expertise, independence, level of education and work experience had a positive and significant effect on the performance of BPR cash supervisors. This indicates that the higher the professional expertise of the cash supervisor, the higher the independence attitude of the cash supervisor, the higher the level of education and the higher work experience a cash supervisor has, the more the performance of the BPR's cash supervisor in BPR Lestari Bali. Keywords: Professional Expertise; Independence; Education; Experience; The performance.